PENGARUH JENIS BURUNG PUYUH DENGAN PEMBERIAN PAKAN KOMERSIAL YANG BERBEDA TERHADAP PERSENTASE KARKAS DAN ORGAN DALAM BURUNG PUYUH (Coturnix-coturnix japonica) - Bayu Aji Pradikdo; Edhy Sudjarwo; Muharlien Muharlien (TERNAK TROPIKA Journal of Tropical Animal Production, 2016)
The purpose of the research was to determine the effect of combination of quail type and different commercial feed treatment. The material used for this research are 96 female Bangkok quail and Bangkok-Local Crossbreed (15 days). The variables are carcass and giblet percentages (heart, liver, spleen and gizzard). The method used in this research is Completely Randomize Design (CRD) by factorial design (2x3). The treatment consists of 2 combinations;  factor A1 (Bangkok) and A2 (Bangkok-Local crossbred). The commercial feed consists of B1 (brand commercial feed A), B2 (brand commercial feed B), B3 (brand commercial feed C). The data collection are in the age 15 days until 63 days. The data are analized by ANOVA (analysis of variant) and continued by Duncan Multiple Range Test. The result shows that interaction of the type of quail and different commercial feed are not significantly influenced (P>0.05) on carcass and giblet percentages. The treatment of type of quail is significantly different (P<0.05) on carcass and liver percentages. The different of commercial feed is not significantly influenced (P>0.05) on carcass and giblet percentages. This research concludes Bangkok quail and brand commercial feed A is able to produce the highest percentage of carcass. Keywords: bangkok quail, crossbreed quail, commercials feed, carcass, hearth